2015
DOI: 10.1016/j.jcrs.2014.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and reproducibility of a new optical biometer in normal and keratoconic eyes

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 18 publications
2
23
0
3
Order By: Relevance
“…Yagci et al showed high repeatability of CCT values by the AL-Scan in both normal and keratoconic groups. Although its reproducibility was not better than other available Scheimpflug systems, the AL-Scan showed excellent and comparable repeatability and reproducibility in most ocular parameters' measurements [ 10 12 , 24 , 25 ]. Thus, it was useful to review and compare the currently used devices such as Pentacam (Oculus, Wetzlar, Germany), Galilei (Ziemer, Port, Switzerland), and Sirius (Costruzione Strumenti Oftalmici, Florence, Italy) as they all use the principle of the Scheimpflug imaging to measure the CCT despite the lack of direct comparison between the AL-Scan and other Scheimpflug systems.…”
Section: Discussionmentioning
confidence: 97%
“…Yagci et al showed high repeatability of CCT values by the AL-Scan in both normal and keratoconic groups. Although its reproducibility was not better than other available Scheimpflug systems, the AL-Scan showed excellent and comparable repeatability and reproducibility in most ocular parameters' measurements [ 10 12 , 24 , 25 ]. Thus, it was useful to review and compare the currently used devices such as Pentacam (Oculus, Wetzlar, Germany), Galilei (Ziemer, Port, Switzerland), and Sirius (Costruzione Strumenti Oftalmici, Florence, Italy) as they all use the principle of the Scheimpflug imaging to measure the CCT despite the lack of direct comparison between the AL-Scan and other Scheimpflug systems.…”
Section: Discussionmentioning
confidence: 97%
“…The precision of AL measurement is currently a hot topic. The PCI biometer was reported to have high repeatability for AL measurement in children [27][28][29][30]. Kimura et al [28] found that the repeatability for AL measurement in myopic children was ± 0.05 mm with the PCI biometer.…”
Section: Discussionmentioning
confidence: 99%
“…ise keratokonus hastalarında AL-Scan ölçümlerinin güvenilir ve tekrarlanabilir olduğunu bildirmiş-lerdir. 20 AL-Scan ve IOL Master optik biyometri cihazları ile elde edilen ölçümlerin karşılaştırıldığı başka bir çalışmada, diğer çalışmalardan farklı olarak absolü hata ve hedef refraksiyondan sapma değerleri de değerlendirilmiş ve AL-Scan ile elde edilen ortalama sferik eşdeğer hatanın 0,03±0,51 olarak ölçüldüğü ve hastaların %64'ünün ±0,50 D aralığında, %96'sının ±1,00 D aralığında saptandığı bildirilmiştir. IOL Master ile elde edilen biyometrik ölçümler ve sferik eş-değer hata arasında fark olmadığı ve daha objektif veriler için ileri çalışmalara ihtiyaç olduğu ŞEKİL 5: Refraktif sapma ile ön kamara derinliği arasındaki ilişki.…”
Section: Discussionunclassified